Forest edges have high conservation value for bird communities in mosaic landscapes - Terraube J; Archaux F; Deconchat M; van Halder I; Jactel H; Barbaro L (WILEY-BLACKWELL, 2022)
A major conservation challenge in mosaic landscapes is to understand how trait-specific responses to habitat edges affect bird communities, including potential cascading effects on bird functions providing ecosystem services to forests, such as pest control. Here, we examined how bird species richness, abundance and community composition varied from interior forest habitats and their edges into adjacent open habitats, within a multi-regional sampling scheme. We further analyzed variations in Conservation Value Index (CVI), Community Specialization Index (CSI) and functional traits across the forest-edge-open habitat gradient. Bird species richness, total abundance and CVI were significantly higher at forest edges while CSI peaked at interior open habitats, i.e., furthest from forest edge. In addition, there were important variations in trait-and species-specific responses to forest edges among bird communities. Positive responses to forest edges were found for several forest bird species with unfavorable conservation status. These species were in general insectivores, understorey gleaners, cavity nesters and long-distance migrants, all traits that displayed higher abundance at forest edges than in forest interiors or adjacent open habitats. Furthermore, consistently with predictions, negative edge effects were recorded in some forest specialist birds and in most open-habitat birds, showing increasing densities from edges to interior habitats. We thus suggest that increasing landscape-scale habitat complexity would be beneficial to declining species living in mosaic landscapes combining small woodlands and open habitats. Edge effects between forests and adjacent open habitats may also favor bird functional guilds providing valuable ecosystem services to forests in long-standing fragmented landscapes.